DNA damage bypass operates in the S and G2 phases of the cell cycle and exhibits differential mutagenicity - Diamant, Noam; Hendel, Ayal; Vered, Ilan; Carell, Thomas; Reißner, Thomas; de Wind, Niels; Geacinov, Nicholas; Livneh, Zvi (Nucleic acids research, 2012)
Translesion DNA synthesis (TLS) employs low-fidelity DNA polymerases to bypass replication-blocking lesions, and being associated with chromosomal replication was presumed to occur in the S phase of the cell cycle. Using immunostaining with anti-replication protein A antibodies, we show that in UV-irradiated mammalian cells, chromosomal single-stranded gaps formed in S phase during replication persist into the G2 phase of the cell cycle, where their repair is completed depending on DNA polymerase ζ and Rev1. Analysis of TLS using a high-resolution gapped-plasmid assay system in cell populations enriched by centrifugal elutriation for specific cell cycle phases showed that TLS operates both in S and G2. Moreover, the mutagenic specificity of TLS in G2 was different from S, and in some cases overall mutation frequency was higher. These results suggest that TLS repair of single-stranded gaps caused by DNA lesions can lag behind chromosomal replication, is separable from it, and occurs both in the S and G2 phases of the cell cycle. Such a mechanism may function to maintain efficient replication, which can progress despite the presence of DNA lesions, with TLS lagging behind and patching regions of discontinuity.